Four Methods Implementing the Inculturation of Nusantara Architecture for Catholic Church Building in Jakarta - Wijayanti, Dinar Ari; Rilatupa, James ED; Sudarwani, M. Maria (Syntax Corporation, 2025)
The architecture of the Nusantara is highly diverse and efforts to delve into it have been extensive. This research aims to discover and develop methods to determine the appropriate style of Nusantara architecture for realizing a Catholic church building in Jakarta, considering religious aspects, urban and societal aspects, cultural inculturation, and the quality of Jakarta's urban environment. The benefits of this research include ensuring that Catholic places of worship in Jakarta reflect local character while also meeting the norms of Catholic liturgy and contributing to sustainable urban development. The scope of this research is divided into two parts: discussion of the variables of planning Catholic worship buildings as dependent variables and free variables related to culture. This research is analytical with a descriptive qualitative approach through observation, surveys, and case studies of two Catholic churches in Jakarta that apply Nusantara architectural styles. The results of this research are four methods of inculturating Nusantara architecture that can be applied to the design of Catholic church buildings in Jakarta: typology method, dynamic equivalence method, assimilation method, and dynamic development method. The methods generated in this research can generally be applied to select Nusantara architectural styles for Catholic church buildings in other regions.